Properties and characterizations of convex functions on time scales - Lara, Teodoro; Merentes, Nelson; Rosales, Edgar; Tineo, Ambrosio (Annales Mathematicae Silesianae, 2018)
In this research we deal with algebraic properties and characterizations of convex functions in the context of a time scale; this notion of convexity has been studied for some other authors but the setting of properties are establish here. Moreover, characterizations, a separation theorem and an inequality of Jensen type for this class of functions are shown as well.